Optimization media from low-cost nutrient sources for growing Spirulina platensis and carotenoid production Optimasi media dengan sumber nutrisi murah untuk pertumbuhan dan produksi karotenoid Spirulina platensis - . TRI-PANJI; . SUHARYANTO (E-Journal Menara Perkebunan, 2001)
SummarySpirulina platensis is a cyanobacteriaproducing several bioactive compounds such ascarotenoids which are economically valuable. Toproduce carotenoids in S. platensis biomassefficiently, it is necessary to define an optimummedium composition consisting of mineral saltand organic complex derived from low-costnutrient sources. Spirulina platensis grown oncomplex media containing latex serum fromconcentrated latex factory, supplemented withsalt minerals might produce high yieldingcarotenoids. The objective of this research is todefine media composition for optimum growthand carotenoid production of S. platensis and toidentify carotenoid compounds from biomass ofthe algae. S. platensis was grown on mediacontaining latex serum from latex concentratefactory (5%, v/v), macroelements andmicroelements, for 10 weeks at a room aeratedand illuminated by 20 W TL lamp at 50 cmdistance. Microelements were formulatedat a certain amount to give eleven combinationsof C: N: P: Mg. The Aiba & Ogawa syntheticmedium was used as a reference medium. Theoptimum growth of S. platensis had reachedafter eight-week incubation. Among elevenmedia composition containing latex serumexamined, best growth on a formulated mediumwith a ratio of C: N: P: Mg = 1:3:0.3:0.2 yielding0.350 g biomass/L This amount was slightlylesser than those on synthetic Aiba & Ogawamedium that yields 0.407 g biomass/L, aftereight-week incubation. Although the biomassproduction was lower than that of synthetic Aiba & Ogawa medium, the formulated mediagave higher carotenoid content. The highestcarotenoid content in biomass was 2.866 mg/kgbiomass obtained from a medium with ratio ofC: N: P: Mg = 1: 2: 0.3: 0. Thin layerchromatography (TLC) analysis of biomassextract showed the presence of two-six carotenoidcompounds, in which one of them is β- carotene.RingkasanSpirulina platensis adalah sianobakteria yangmenghasilkan berbagai senyawa bioaktif bernilaiekonomi tinggi antara lain karotenoida. Untukmemproduksi karotenoida dari biomassa selS. platensis secara efisien, perlu ditetapkankomposisi media mineral dan bahan organikkompleks yang optimal dari sumber nutrisi yangmurah. Spirulina platensis yang ditumbuhkandalam media serum lateks dari pabrik latekspekat dengan suplemen garam-garam mineraltertentu diharapkan produktif dalammenghasilkan karotenoida. Tujuan penelitianadalah menetapkan komposisi media yangoptimal untuk pertumbuhan dan produksikarotenoid serta mengidentifikasi jenis senyawakarotenoid dalam biomassa sel S. platensis.Sianobakteria ini ditumbuhkan dalam mediakompleks mengandung serum lateks pekat(5%, v/v) dengan suplemen nutrisi berupamakronutrien dan mikronutrien selama10 minggu di dalam ruangan dengan aerasi danpenyinaran lampu TL 20 W pada jarak 50 cm.Komposisi makronutrien diformulasi untukmemberikan sebelas macam variasi nisbahC:N:P:Mg. Sebagai pembanding digunakanmedia sintetik Aiba & Ogawa. Hasil penelitianmenunjukkan bahwa pertumbuhan S. platensismencapai puncak setelah diinkubasikan selamadelapan minggu. Dari 11 komposisi mediamengandung lateks yang diuji, pertumbuhanS. platensis terbaik adalah yang ditumbuhkandalam media formula dengan nisbah C:N:P:Mg=1:3:0.3:0.2 menghasilkan 0,350 g biomassa/L,sedikit lebih rendah dibandingkan denganmenggunakan media sintetik Aiba & Ogawa yangmenghasilkan 0,407 g biomassa/L selama8 minggu. Walaupun kandungan biomassanyalebih rendah, media formula tersebut meng-hasilkan karotenoid lebih tinggi dibandingkandengan media sintetik Aiba & Ogawa.Kandungan karotenoid tertinggi pada biomassayaitu sebesar 2.866 mg/kg diperoleh pada mediadengan nisbah C:N:P:Mg=1:2:0.3:0. Analisisekstrak biomassa dengan TLC menunjukkanadanya dua-enam jenis karotenoida, salahsatunya adalah β - karotena.